Prenatal and postnatal psychological symptoms of parents and family functioning: the impact on child emotional and behavioural problems - Velders, Fleur P. (Springer-Verlag, 2011)
Although relations of various parental psychological problems and family functioning with child development are well documented, it remains unclear whether specific prenatal or specific postnatal risk factors are independently associated with child emotional and behavioural problems, or whether observed associations can be explained by general parental psychopathology. Using a stepwise approach, we examined the effects of prenatal and postnatal parental depressive symptoms, prenatal and postnatal hostility of the parents, as well as prenatal family functioning on the risk of child emotional and behavioural problems. This study was embedded in Generation R: a population-based cohort from foetal life onwards. Mothers and fathers of 2,698 children provided information about depressive symptoms, symptoms of hostility and family functioning during pregnancy and 3 years after birth. Mother and father each reported on child behaviour when the child was 3 years old. Parental depressive symptoms increased the risk of child emotional and behavioural problems, but this increase was explained by postnatal parental hostile behaviour. Postnatal symptoms of hostility of mothers (OR = 1.34, p value <0.001) and postnatal symptoms of hostility of fathers (OR = 1.30, p value <0.001) each contributed independently to the risk of child emotional and behavioural problems. Postnatal parental hostility is associated with an increased risk of child emotional and behavioural problems, independent of parental depressive symptoms. These findings suggest that prevention and intervention strategies should focus on psychological symptoms of both mothers and fathers, in particular on hostile behaviour, in families with young children. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00787-011-0178-0) contains supplementary material, which is available to authorized users.